A dynamic organic Rankine cycle using a zeotropic mixture as the working fluid with composition tuning to match changing ambient conditions. (1st June 2016) - Collings, Peter; Yu, Zhibin; Wang, Enhua
Highlights: A dynamic ORC using a zeotropic mixture with composition tuning is proposed. The working principle is verified theoretically, based on a thermodynamic model. Improvements in the resultant power plant's annual power production are analysed. The economic benefits have been demonstrated by an economic analysis. Abstract: Air-cooled condensers are widely used for Organic Rankine Cycle (ORC) power plants where cooling water is unavailable or too costly, but they are then vulnerable to changing ambient air temperatures especially in continental climates, where the air temperature difference between winter and summer can be over 40 °C. A conventional ORC system using a single component working fluid has to be designed according to the maximum air temperature in summer and thus operates far from optimal design conditions for most of the year, leading to low annual average efficiencies. This research proposes a novel dynamic ORC that uses a binary zeotropic mixture as the working fluid, with mechanisms in place to adjust the mixture composition dynamically during operation in response to changing heat sink conditions, significantly improving the overall efficiency of the plant. The working principle of the dynamic ORC concept is analysed. The case study results show that the annual average thermal efficiency can be improved by up to 23% over a conventional ORC when the heat source is 100 °C, while the evaluated increase of the capital cost is less than 7%. The dynamic ORC power plants are particularly attractive for low temperature applications, delivering shorter payback periods compared to conventional ORC systems.